Cystic Fibrosis Pulmonary Exacerbations Attributable to Respiratory Syncytial Virus and Influenza: A Population-Based Study - Somayaji, Ranjani (Clin Infect Dis, 2017)
BACKGROUND. Characterization of the role of respiratory viral pathogens on cystic fibrosis (CF) pulmonary disease is needed. We aimed to determine the association of influenza and respiratory syncytial virus (RSV) activity with risk of pulmonary exacerbation (PEx) in persons with CF in the United States. METHODS. We conducted a cohort study from January 2003 to March 2009 using the CF Foundation Patient Registry merged with Centers for Disease Control and Prevention respiratory virus surveillance data. The primary goal was to determine the association between regional influenza or RSV detections with risk of PEx requiring intravenous antibiotics or hospitalization. We analyzed outcomes by geographic region and week of event using multivariable regression models adjusted for demographic and clinical predictors of PEx stratified for children (<18 years) and adults (≥18 years) to calculate relative risks (RRs) of PEx. RESULTS. There were 21022 individuals (52% male) in the CF patient cohort in 2003 comprised of 12702 children and 8320 adults. The overall incidence rate of PEx was 521.9 per 10000 person-months. In children, a 10% increase in the proportion of surveillance tests positive for influenza or RSV was significantly associated with increased PEx risk (RR, 1.02; 95% confidence interval [CI], 1.01–1.03) and (RR, 1.05; 95% CI, 1.02–1.07), respectively. In adults, surveillance tests positive for influenza (RR, 1.02; 95% CI, 1.01–1.02), but not RSV (RR, 0.99; 95% CI, .98–1.01), had a significant association with PEx risk. CONCLUSIONS. Our large CF population–based cohort demonstrated a significant association between PEx risk and influenza activity in children and adults and with RSV activity in children.